2012
DOI: 10.1128/jvi.06993-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of O-Glycosylation and Expression of CD43 and CD45 on the Surfaces of Effector T Cells in Human T Cell Leukemia Virus Type 1 Cell-to-Cell Infection

Abstract: We used replication-dependent retroviral vectors to identify cell surface antigens involved in the cell-to-cell transmission of human T cell leukemia virus type 1 (HTLV-1). We generated monoclonal antibodies ( H uman T cell leukemia virus type 1 (HTLV-1) is a deltaretrovirus that causes two major diseases, adult T cell leukemia (ATL) (29) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) (1, 51). Unlike HIV-1, which causes fatal immune deficiency-associated diseases in almost all infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Using a panel of lectins and MAbs these authors have also determined glycoproteins that are concentrated at viral assemblies, particularly, the extracellular matrix proteins collagen and agrin, the linker proteins tetherin and galectin-3. In our previous study, we have shown the importance of O-glycan bearing molecules, CD43 and CD45, for cell adhesiveness and transmission of HTLV-1 (Mazurov et al, 2012). As VB structures are enriched with highly glycosylated proteins, we believe that our published data support the model of virus transmission via VB.…”
Section: Introductionsupporting
confidence: 67%
“…Using a panel of lectins and MAbs these authors have also determined glycoproteins that are concentrated at viral assemblies, particularly, the extracellular matrix proteins collagen and agrin, the linker proteins tetherin and galectin-3. In our previous study, we have shown the importance of O-glycan bearing molecules, CD43 and CD45, for cell adhesiveness and transmission of HTLV-1 (Mazurov et al, 2012). As VB structures are enriched with highly glycosylated proteins, we believe that our published data support the model of virus transmission via VB.…”
Section: Introductionsupporting
confidence: 67%
“…Nonetheless, it is conceivable that a specific UDM protein modulates HIV-1 release or cell-to-cell transmission. For example, a recent study showed that increased expression of the UDM protein CD43 correlates with enhanced cell-to-cell transmission of HTLV-1, another retrovirus that replicates in T cells (100). Thus, although it is not known whether association of CD43 and HTLV-1 in microdomains plays a role in this increase of cell-tocell transmission, it is conceivable that specific UDMs or UDMassociated proteins contribute to cell-to-cell transmission of HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…The cell coculture infection assay was performed in lymphoid cells as described previously (9,13). Briefly, 10 6 CEM cells were electroporated with 3 g of pUCHR-inGFPt and/or 3 g of pUCHR-inmCherry vector DNA and 2 g of pCMV⌬8.2R plasmid DNA in the presence or absence of 0.8 g of the pIIINL-4env plasmid, which expresses Env from HIV-1 strain NL4-3 (16).…”
Section: Methodsmentioning
confidence: 99%
“…Vector pGIPZ-P1 containing shRNA targeting phosphoprotein-1 (P1) of respiratory syncytial virus (RSV) has been described previously (13) and was used as a control. The DNA sequences of the miR30-based shRNAs were amplified from the pGIPZ plasmids by PCR with primers 5=-CGTCTAGATGTTTGAATGAGGCTTCAGTA C-3= and 5=-CGTCTAGAAGTGATTTAATTTATACCATTTTAATTC-3= and inserted into the intron at the XbaI site.…”
Section: Methodsmentioning
confidence: 99%